1992
DOI: 10.1021/jf00022a027
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber from mango byproducts: Characterization and hypoglycemic effects determined by in vitro methods

Abstract: Mango (Mangifera indica L.) byproducts, which represent 35-60 % of the processed fruit, are a potential source of dietary fiber. After ethanolic purification, we found that peels and fibrous waste pulp had a high dietary fiber content (74% of the dry matter) with a soluble/insoluble ratio close to 1 and a 15-20 % uronic acid content. The fiber water-soluble fraction showed shear-thinning behavior. In vitro studies indicate that these fibers decreased total starch digestibility and slowed the final rate of amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 21 publications
1
52
1
2
Order By: Relevance
“…According to them the significant antihyperglycemic effect may be due to the potentiating of plasma Insulin effect by increasing either the pancreatic secretion of insulin from the existing β-cells or its release from the bound Form, as evidenced by the significant increase in the level of insulin by C. ficifolia fruit extract in diabetic rats [10]. in other study Gourgue and Champ and their colleagues in 1992 showed that pectin, as an important component of plant cell walls, a water-soluble fiber is found in abundance in squash and The presence of pectin itself in the squash is considered as a hypoglycemic factor [17]. Based on the results of Kazemiand her colleagues research in1389 which were performed on 28 rats it has been proved that the average size of pancreatic islets in the group treated with pumpkin compared to the diabetic group was increased.…”
Section: Results: Discussionmentioning
confidence: 98%
“…According to them the significant antihyperglycemic effect may be due to the potentiating of plasma Insulin effect by increasing either the pancreatic secretion of insulin from the existing β-cells or its release from the bound Form, as evidenced by the significant increase in the level of insulin by C. ficifolia fruit extract in diabetic rats [10]. in other study Gourgue and Champ and their colleagues in 1992 showed that pectin, as an important component of plant cell walls, a water-soluble fiber is found in abundance in squash and The presence of pectin itself in the squash is considered as a hypoglycemic factor [17]. Based on the results of Kazemiand her colleagues research in1389 which were performed on 28 rats it has been proved that the average size of pancreatic islets in the group treated with pumpkin compared to the diabetic group was increased.…”
Section: Results: Discussionmentioning
confidence: 98%
“…The highest inhibitory activity (47.9%) of AIS implied that the amylase-inhibiting substances present in the carambola pomace might be alcohol-insoluble (or watersoluble). From the findings of Gourgue et al [5] and Ou et al [15], fibres could retard a-amylase activity through embedding starch and enzyme, and even inhibit the enzyme. In this study, the abilities of these FRFs to adsorb glucose and reduce amylase activity implied that they might help decrease the rate of glucose absorption and the concentration of postprandial serum glucose.…”
Section: Resultsmentioning
confidence: 98%
“…All of these FRFs were determined on weight basis, and were not corrected for protein and ash (13.6-20.2 g/100 g of FRF) ( Table 3). For the by-products from citrus fruits, mango, and quince, their AIS contents were found to be 45.0-75.0, 30.7-49.7, and 27.8-37.5 g/ 100 g, respectively [5,8,19]. In addition to the carbohydrate fraction, FRFs might also contain protein, ash, polyphenols, and lignin in different extent [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This exception could be due to variation in the non sweet sugar components constituting the fiber samples. Another possible reason for amylase inhibition not being in accordance with the insoluble dietary fiber content might be due to the reduced accessibility of the enzyme to their substrate because of the encapsulation of starch and enzyme by the fiber (Ou et al 2001;Gourgue et al 1992). Amylase inhibition property of the fiber samples indicates their positive role in delaying the rate of glucose absorption in the intestine due to delayed release of glucose from starch digestion which ultimately lowers postprandial serum glucose (Chau et al 2003).…”
Section: Functional Propertiesmentioning
confidence: 99%